Costa Rica : Technical Assistance Report-The National Accounts Statistics Capacity Development Mission. (IMF Staff Country Reports; Country Report, 2020)
A technical assistance (TA) mission, conducted by CAPTAC-DR, took place during August 27 to September 7, in San Jose, Costa Rica, to assist the Central Bank of Costa Rica (CBCR) in compiling the non-financial and financial balance sheets. This TA mission was requested in the context of the rebasing project of the national accounts series to 2017, as follow-up of a previous mission conducted in March 2018. This mission covered two purposes: 1) provide guidance to the CBCR in developing statistical methods to estimate the capital stock for the non-financial private sector (NFPS), and 2) provide TA in compiling balance sheets, as part of the annual accounts by institutional sector (AAIS) of Costa Rica.